Histopathologic pattern of posterior cranial Fossa tumours in a West African tertiary (2019)
Introduction: The posterior cranial fossa contains many vital structures and mortality of patients with tumours occurring in this area is high. Studies done in other geographic locations showed a higher occurrence of posterior cranial fossa tumours in paediatric patients while benign tumours were more commonly seen. Epidemiological data of tumours in this area in our environment is scarce. This study was done to ascertain the histopathologic pattern of tumours in the posterior cranial fossa in a predominantly black population. Method: A ten-year retrospective study of histologically diagnosed posterior cranial fossa tumours seen in our hospital facility was done. A total of 72 cases in which neurosurgical intervention was carried out were identified and this included all age groups. The age, sex, site of tumour and histological diagnosis were extracted from the patients' records. Result: Adult patients predominated with 55.6% while the paediatric patients were 44.4%. The male to female ratio in the paediatric patients was 2.56:1 but the ratio was equal in the adult patients. WHO grade 1 tumours were the commonest tumours seen (45.8%) while grade II tumours were the least (4.2%). Medulloblastomas (20.83%), Pilocytic astrocytomas (18.6%) and Meningiomas (8.33%) were the commonest tumours seen. Commonest locations are in the cerebellar hemispheres (56.9%) and the fourth ventricle (13.89%). Conclusion: Our study showed a higher occurrence of Medulloblastomas in contrast to other studies which have shown more of Schwannomas, a tumour type that was rare in this study. The relatively low number of metastatic tumours in this study may be due to lack of presentation of such patients.